A Study of The Local Toxicity of Agents Used for Variceal Injection Sclerotherapy. Issue 2 (1989) - Robertson, C. S.; Womack, C.; Robson, K.; Morris, D. L.
Abstract : Injection sclerotherapy is widely used in the treatment of oesophageal varices. However, few studies have compared the local toxicity of sclerosant agents which may be important if serious local complications are to be avoided. In this study the depth of injury caused by submucosal injection of increasing concentrations of sodium tetradecyl sulphate, polidocanol, 5% ethanolamine oleate and 5% varicosid in rabbits stomach, has been compared by histopathological examination. Macroscopic ulceration was seen in 14.6% of injection sites. Increasing concentrations of sodium tetradecyl sulphate and polidocanol produced increasingly extensive microscopic inflammation. Five percent varicosid caused more inflammation than 5% ethanolamine and only 3% polidocanol and 5% varicosid caused full thickness inflammation. Only 5% ethanolamine produced inflammation consistently confined to the mucosa and submucosa. On the basis of this study we feel that 5% ethanolamine is the most suitable agent for injection sclerotherapy.